2014
DOI: 10.1080/10410236.2013.856741
|View full text |Cite
|
Sign up to set email alerts
|

Physician Communication in the Operating Room

Abstract: In this study, communication research was conducted with multidisciplinary groups of operating-room physicians. Theoretical frameworks from intercultural communication and rhetoric were used to (a) measure latent cultural communication variables and (b) conduct communication training with the physicians. A six-step protocol guided the research with teams of physicians from different surgical specialties: anesthesiologists, general surgeons, and obstetrician-gynecologists (n = 85). Latent cultural communication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Happens becaus of workload, lack of support, culture Frequency and effects of rude communication When exposed to rude, dismissive, aggressive behavior mistakes are made endangering patient safety and making staff feel sad, angry and demotivated Fatahi, Krupic, and Hellström (2015) 49 Sweden Focus groups Consultation Radiology Study radiologists’ experiences of written and oral communication with referring clinicians and its potential implications for decision making and patient care Radiologists emphasize sufficient use of a communication tool. And a preference for oral instead of written communication - - Kirschbaum et al (2015) 16 ) USA Pre- and posttest survey (n = 85) Communication Anesthesiology / Surgery / Obstetrics / Gynecology Measure the effect of multidisciplinary communication training on latent variables of communication Significant increase and decrease in scores supporting more participatory communication and teamwork after training, especially among surgical physicians. Variance in pre training scores of conflict style for each physician group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Happens becaus of workload, lack of support, culture Frequency and effects of rude communication When exposed to rude, dismissive, aggressive behavior mistakes are made endangering patient safety and making staff feel sad, angry and demotivated Fatahi, Krupic, and Hellström (2015) 49 Sweden Focus groups Consultation Radiology Study radiologists’ experiences of written and oral communication with referring clinicians and its potential implications for decision making and patient care Radiologists emphasize sufficient use of a communication tool. And a preference for oral instead of written communication - - Kirschbaum et al (2015) 16 ) USA Pre- and posttest survey (n = 85) Communication Anesthesiology / Surgery / Obstetrics / Gynecology Measure the effect of multidisciplinary communication training on latent variables of communication Significant increase and decrease in scores supporting more participatory communication and teamwork after training, especially among surgical physicians. Variance in pre training scores of conflict style for each physician group.…”
Section: Resultsmentioning
confidence: 99%
“… 15 , 49 , 73 In eight studies, a difference between medical specialities was found, with some being more prone to collaborate or rated higher for collaboration and others more likely to express negative behaviours. 3 , 15 , 16 , 26 , 31 , 36 , 37 , 61 A clear overview of which medical speciality is more likely to be collaborative cannot be provided, as most studies only focus on some specific specialties. Remarkably, specialties that are more likely to engage in negative behaviours (radiology, surgery, cardiology) are more often the targeted specialties in studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Silence can also be an avoidant conflict style, associated with attempts to protect one’s self-image within a strong hierarchical structure without being exposed as lacking in knowledge [ 47 , 48 ]. The hierarchical structure in the medical discourse can contribute to participants’ silence (and/or avoidance) rather than a participatory teamwork communication [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The major advantage is that the recordings allowed us to repeatedly observe the audio-and video-recorded material. However, the cameras did not always include the entire field of view in the emergency room, and could not record events occurring off the screen [ 49 ]. The participants’ work was performed within a limited area around the patient simulator, meaning that other team members could stand in the way of the camera and thereby complicate the analysis.…”
Section: Discussionmentioning
confidence: 99%